MORAL RIGHTS IN THE CASE OF DOCTORAL THESES. LIMITATIONS OF MORAL RIGHTS - Ionuț Cătălin TIRITEU (Challenges of the Knowledge Society)
This study attempts an analysis of the doctoral thesis from the perspective of copyright, specifically examining the prerogatives and limitations of copyright when a doctoral thesis is created. In this regard, the doctoral thesis is defined, and it is specified whether it benefits from moral copyright and what the concept and legal characteristics of moral copyright are. The legal framework is provided, and the most relevant doctrinal opinions are analysed, along with several examples from case law. Emphasis is placed on the content of moral copyright in the case of doctoral theses and their limitations.